Miracle et espace social au village nahua de La Esperanza, Mexique - Anath Ariel de Vidas (Ateliers d'Anthropologie)
The story of a miracle on the mountain near the Nahua village of La Esperanza, in the Veracruzan Huasteca in Mexico, constitutes the only narrative offered in this village on the subject of its foundation. This narrative, far from being rooted in ancient times, is explicitly set in the middle of the 20th century and tells of offerings to the mountain, ending several years of drought. And yet, the analysis of this single mythical story ultimately helps shed light on the historical story of the village. It simultaneously reveals the fragmentation and delimitation of the social and political boundaries of the local Indian group.